PENGARUH CUSTOMERVALUEDANCUSTOMER SATISFACTION TERHADAP CUSTOMERLOYALTY PRODUK-PRODUK INDUSTRI KECIL DI DESA TAMBAK SEGORO SIDOARJO - Asjari, Fachrudy; Surabagiarta, I Ketut (Fakultas Ekonomi Universitas PGRI Adi Buana, 2015)
This research intended to assess the Customer Value, Customer Satisfaction to The Customer Loyalty which must be performed to the product of small industry in Tambak Segoro Village Sidoarjo. This research was conducted in Sidoarjo which covered 25 customers as respondent. This research by utilizing Regression, the technique was processed with SPSS 18.0 to analyze some hypothesis. The inter correlations models between three variables in this study revealed that the hypothesis have significant correlation. The result of this research were empirical date of the development of the theoretical of marketing and practice management.